1967
DOI: 10.1099/00221287-48-2-293
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Two Antibacterial Products of the Marine Planktonic Alga Isochrysis galbana

Abstract: SUMMARYThe acetone-extractable antibacterial components of Zsochrysis galbana have been resolved by paper-chromatography and bioautography. Two pigmented products with similar antibacterial properties were obtained which were tentatively identified from their absorption spectra as chlorophyll a derivatives, probably pheophytin a and an atypical chlorophyllide a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 7 publications
(5 reference statements)
0
13
0
Order By: Relevance
“…Similar to these fatty acids, aand c-linolenic acid also showed antibacterial activity towards methicillin-resistant Staphylococcus aureus (MRSA) (Ohta et al 1994). Other antibacterial compounds produced by microalgae include glycosides, terpenes (Seraspe et al 2005), polyunsaturated aldehydes (Ribalet et al 2008) and chlorophyll a derivatives (Bruce et al 1967). Whether the antibacterial activity of these compounds is limited to certain bacterial species or whether it is broad-spectrum remains to be investigated.…”
Section: Chlorella Vulgarismentioning
confidence: 99%
“…Similar to these fatty acids, aand c-linolenic acid also showed antibacterial activity towards methicillin-resistant Staphylococcus aureus (MRSA) (Ohta et al 1994). Other antibacterial compounds produced by microalgae include glycosides, terpenes (Seraspe et al 2005), polyunsaturated aldehydes (Ribalet et al 2008) and chlorophyll a derivatives (Bruce et al 1967). Whether the antibacterial activity of these compounds is limited to certain bacterial species or whether it is broad-spectrum remains to be investigated.…”
Section: Chlorella Vulgarismentioning
confidence: 99%
“…1). The majority of these studies focused on the role of antibacterial substances in ecological interactions (Sieburth 1959;Burkholder et al 1960;Jorgensen & Nielsen 1961;Duff et al 1966;Bruce et al 1967;Ramamurthy 1970;Berland et al 1972). For example, Sieburth (1959) observed that a microalgal species from the Antarctic was able to release substances into the medium that reduced bacterial growth [Escherichia coli Migula (Castellani & Chalmers)] as well as modified the gastrointestinal flora of penguins that ingested the microalgae.…”
Section: Investigation Of Antibacterial Activity Of Microalgae -An Ovmentioning
confidence: 98%
“…Among the antibacterial compounds that have been identified from eukaryotic microalgae are acrylic acid (Sieburth 1960), fatty acids (Pratt et al 1944;Findlay & Patil 1984;Ohta et al 1994;Desbois et al 2008) and pigments such as carotenoids and chlorophylls and their derivatives (Bruce et al 1967;Bhagavathy et al 2011). The isolation and identification of compounds are extremely important to evaluate their novelty and effectiveness.…”
Section: Antibacterial Activity Of Eukaryotic Microalgaementioning
confidence: 99%
“…Finally, Bruce et al . [190] also reported the isolation of two chlorophyll a derivatives, which are active against Gram-positive and Gram-negative marine bacteria.…”
Section: Unconventional Anti-infectivesmentioning
confidence: 99%